2019
DOI: 10.14233/ajchem.2019.21952
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Studies of Hexamethyldibenzotetraaza N4-Macrocyclic Complexes of Ni(II) and Cu(II) Metal ions

Abstract: Hexamethyldibenzotetraaza[14]annulene type macrocyclic complexes of Ni(II) and Cu(II) have been synthesized by template method. These macrocyclic complexes were characterized by molar conductance, elemental analysis, IR, UV-visible, mass spectra and cyclic voltammetry. On the basis of electronic studies saddle shape distorted octahedral structure have been assigned to these macrocyclic complexes. The redox behaviour of Ni(II) and Cu(II) macrocyclic complexes showed reversible and quasi-irreversible redox proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previously, comprehensive research on the development of macrocyclic complexes has evolved with particular respect to their antibacterial activity. Transition metal macrocyclic complexes were extensively examined for their antimicrobial and anticancer properties [16][17][18][19].…”
Section: Coordination Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, comprehensive research on the development of macrocyclic complexes has evolved with particular respect to their antibacterial activity. Transition metal macrocyclic complexes were extensively examined for their antimicrobial and anticancer properties [16][17][18][19].…”
Section: Coordination Compoundsmentioning
confidence: 99%
“…Recently, transition metals such as cobalt and nickel have been used for synthesis of complexes with diverse ligand and studied for their diverse properties [5][6][7][8]. In the early electrochemical studies of tetraazamacrocyclic complexes, the factors that influence the development of both oxidized and reduced metal species were identified [9][10][11]. It has been revealed that the overall redox activities of a particular system are determined by the following factor: (i) macrocyclic ring size, (ii) the ligand charge, (iii) the type of the ligand substituents, and (iv) degree of ligand unsaturation.…”
Section: Introductionmentioning
confidence: 99%